PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA PEJABAT STRUKTURAL DENGAN BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Nugroho, Wasono -; -, Sunarso - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT This study aims to (1) analyze the significance of the effect of participation in budget preparation, organizational culture, and organizational commitment to performance structural officer. (2) analyze the effect of participation in the performance of official budgetary structural moderated by organizational culture (3) analyze the effect of budgetary participation on performance are moderated by officials structural organizational commitment. The population in this study were all middle and lower level leaders are involved in the preparation of the budget in as many as Pemerntahan Grobogan District 294 officials. Total sample as a whole by 74 respondents, taken using the technique of "Proportional Cluster Random Sampling". The data collection technique using a questionnaire through validity and reliability. Regression test requirements using classical assumption test. Data analysis techniques using multiple linear regression analysis and regression testing moderating the absolute value of the difference and hypothesis testing conducted by t test. The results show that: (1) participation in the preparation of the budget is not exhibited significantly affect the performance of the officials in the Government District Grobogan structural, (2) organizational culture has a significant effect on the structural performance of the officials in the Government District Grobogan, (3) organizational commitment have a significant influence on the performance District government officials Grobogan structural, (4) there is a significant effect of participation on performance budgeting at the district government officials structural Grobogan moderated by organizational culture, (5) there is a significant effect of budgetary participation on performance structural officials in the Government of the District Grobogan moderated by organizational commitment. Keywords: budget participation, organizational culture, organizational commitment, performance structural officer.